THE METHOD OF CREATING INDEPENDENT EDUCATIONAL ASSIGNMENTS BASED ON THE CREDIT-MODULE SYSTEM FROM CHEMICAL SCIENCES TAUGHT AT THE UNDERGRADUATE LEVEL - Mamadaliyeva Nodira Isakovna; Ibodullayeva Mavjuda Ibodullayevna; Sapayeva Gulzor Islambaevna; Rixsiyeva Umida Shavkat qizi (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This study explores the development and impact of independent educational assignments within the credit-module system for undergraduate chemical sciences. Utilizing a mixed-methods approach, assignments were designed and implemented in a cohort of 120 students, divided into experimental and control groups. Results indicated a significant improvement in the experimental group’s academic performance and engagement. Qualitative feedback revealed higher levels of student satisfaction and enhanced critical thinking skills. Instructors also noted increased proactivity and participation among students.